The Influence of Volunteers’ Psychological Capital: Mediating Role of Organizational Commitment, and Joint Moderating Effect of Role Identification and Perceived Social Support - Xu, Li ping; Wu, Yu shen; Yu, Jing jing; Zhou, Jie (Frontiers in Psychology, 2020)
This study explored the relationship between volunteers’ psychological capital and their commitment to volunteering. We tested whether volunteers’ psychological capital had a positive predictive effect on volunteering and whether this effect was mediated by organizational commitment, role identification, or perceived social support. A sample of 1165 volunteers who were registered in the national volunteer service information system of China was recruited in the study. The results showed a significant and positive relationship between volunteers’ psychological capital, volunteering, role identification, perceived social support, and organizational commitment. Volunteers’ psychological capital not only had a direct effect on volunteering but also affected volunteering through the mediating role of organizational commitment. Additionally, the influence of volunteers’ psychological capital on organizational commitment was affected by the joint moderated effect of role identification and perceived social support. Volunteers with low role identification and low perceived social support, high role identification and low perceived social support, and low role identification and high perceived social support committed to their volunteer organization faster when they had a high level of psychological capital; whereas, volunteers with high role identification and high perceived social support committed to their volunteer organization faster when they had a low level of psychological capital.